Sydenham’s Chorea as Presentation of Rheumatic Heart Disease - Joshi, A.; Shrestha, R.P.B.; Shrestha, P.S.; Dangol, S.; Shrestha, N.C.; Poudyal, P.; Shrestha, A. (Kathmandu University Medical Journal, 2017)
Sydenham’s chorea is the most common type of acquired chorea in childhood which is a major neurological manifestation of rheumatic fever. We describe a 13 years old girl who presented with weakness and purposeless involuntary movements of upper and lower limbs. The symptoms slightly affected the child’s daily activities and had an unstable gait on walking which was aggravated during stress. Grade II ejection systolic murmur was noticed on cardiovascular examination. Echocardiography evaluation showed thickened aortic and mitral valve leaflets with mild to moderate degree of mitral regurgitation. Anti-streptolysin O titer was positive (≥200 IU/ml). CT scan of brain was normal. Subsequently child was diagnosed as Rheumatic heart disease with Sydenham’s chorea and kept on regular Benzathine penicillin prophylaxis. Symptoms subsided spontaneously after 3 months without any further complications. Although decreasing, early diagnosis and management of Sydenham’s chorea and Rheumatic heart disease are very crucial and should be considered with such presentation.